2012
DOI: 10.1111/j.1476-5381.2011.01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation of chemokine receptor function

Abstract: G protein-coupled chemokine receptors and their peptidergic ligands are interesting therapeutic targets due to their involvement in various immune-related diseases, including rheumatoid arthritis, multiple sclerosis, inflammatory bowel disease, chronic obstructive pulmonary disease, HIV-1 infection and cancer. To tackle these diseases, a lot of effort has been focused on discovery and development of small-molecule chemokine receptor antagonists. This has been rewarded by the market approval of two novel chemok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
258
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(271 citation statements)
references
References 209 publications
(320 reference statements)
8
258
0
5
Order By: Relevance
“…They can bind to and block their target protein, that is, direct targeted therapy, or they can influence critical biological processes that is, antibody-dependent cell-mediated cytotoxicity or complement-dependent toxicity. 157 Certain characteristics of chemokine receptors, including their limited availability as purified proteins and low immunogenicity, have hampered the development of novel therapeutic agents. 157 However, following increased interest in this area, neutralizing mAbs have been used to inhibit leukocyte recruitment in a number of disease processes in animal models and have been incorporated into human trials.…”
Section: Chemokines As Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can bind to and block their target protein, that is, direct targeted therapy, or they can influence critical biological processes that is, antibody-dependent cell-mediated cytotoxicity or complement-dependent toxicity. 157 Certain characteristics of chemokine receptors, including their limited availability as purified proteins and low immunogenicity, have hampered the development of novel therapeutic agents. 157 However, following increased interest in this area, neutralizing mAbs have been used to inhibit leukocyte recruitment in a number of disease processes in animal models and have been incorporated into human trials.…”
Section: Chemokines As Therapeutic Targetsmentioning
confidence: 99%
“…157 Certain characteristics of chemokine receptors, including their limited availability as purified proteins and low immunogenicity, have hampered the development of novel therapeutic agents. 157 However, following increased interest in this area, neutralizing mAbs have been used to inhibit leukocyte recruitment in a number of disease processes in animal models and have been incorporated into human trials. A mAb to CXCL8 (ABX-IL8, Abgenix) has been shown to inhibit neutrophil and monocyte infiltration into the lungs of patients suffering from COPD, reducing the severity of dyspnea, but having no influence on lung function or health status.…”
Section: Chemokines As Therapeutic Targetsmentioning
confidence: 99%
“…The 19 known human chemokine receptors and their Ïł50 endogenous peptide ligands form a complex system in which many chemokine receptors can bind multiple chemokines, and many chemokines can bind more than one receptor (1). Chemokine receptors signal predominantly via heterotrimeric G i proteins, resulting in an inhibition of cAMP production by adenylyl cyclases and induction of intracellular calcium mobilization (2).…”
mentioning
confidence: 99%
“…18 CXCL12 binds to CXCR4 via interactions of the N-terminus and the extracellular loop 2 (ECL2). 18 Epitope mapping revealed that the CXCR4 targeting Nbs bind with high affinity and specificity to ECL2. The aspartic acid at position 187, involved in binding of CXCL12, appears to be critical for the CXCR4 targeting Nbs, underlining their competitive behavior.…”
Section: Friday November 25 2016mentioning
confidence: 99%
“…These receptors are therefore attractive therapeutic targets. 18 Via DNA and whole cell immunization of llamas, phage display and counterselection, the first Nbs targeting the extracellular side of GPCRs, and more specifically chemokine receptors, were identified. The CXCR4-specific Nbs antagonize CXCL12-dependent binding and signaling, inhibit HIV-1 replication in vitro and induce stem cell mobilization in vivo.…”
Section: Friday November 25 2016mentioning
confidence: 99%